ANALISIS PENGARUH PEMBERIAN INSENTIF, KEPEMIMPIAN DAN BEBAN KERJA TERHADAP KINERJA PERAWAT (Studi pada Perawat ruang RSUD Kota Semarang) - Bawono, Dimas Ciptoning; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2015)
This study aims to determine the effect of incentives, leadership and work load on the performance of nurses background of the phenomena that occur in the performance of nurses at the General Hospital of Semarang City. This study uses incentives, leadership and workload as independent variables and the performance of nurses as the dependent variable. This research was conducted at the General Hospital of Semarang City, with the data collection method using a questionnaire distributed to 70 nursing rooms General Hospital of Semarang City with a minimum length of work for 3 years.Based on the multiple linear regression test, the results show that the incentives have a positive relationship and a significant influence on the performance of nurses. Leadership has a positive and significant impact on the performance of nurses. While the workload has a positive relationship, but no significant effect on the performance of nurses.